PENGARUH PROMOSI, KUALITAS LAYANAN, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN ULANG PADA MBAKOY COFFEE UNAAHA - Yunila Yunila; Muhammad Pariama; Nanda Apriani (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to empirically examine and analyze the effect of promotion (X1), service quality (X2), and price (X3) on repeat purchase decisions (Y) at Mbakoy Coffee Unaaha. This type of research is quantitative research. The number of respondents in this study were 62 customers of Mbakoy Coffee Unaaha. Multiple linear analysis techniques are used to test the research hypothesis. Data processing was carried out using the SPSS version 25 program. The results of this study indicate that Promotion, Service Quality and Price simultaneously influence Repurchase Decisions at Mbakoy Coffee Unaaha. Promotion partially has a significant effect on the Repurchase Decision at Mbakoy Coffee Unaaha. Service Quality partially has a significant effect on Repurchase Decisions at Mbakoy Coffee Unaaha. Price partially has a significant effect on the Repurchase Decision at Mbakoy Coffee Unaaha. Keywords: Promotion, Service Quality, Price and Repurchase Decision